Two new endophytic fungi of Colletotrichum and Diaporthe isolated from Berchemia polyphylla var. leioclada in Guizhou Province, China - Zhou, Si-Xuan; Bao, Dan-Feng; Zhang, Tao; Xiao, Yuan-Pin; Tang, Yuan-Jiang; Jing, Zhang; Lu, Yu-Xi; Shi, Kai-Zhi (Phytotaxa, 2024)
Berchemia polyphylla var. leioclada is an important traditional Chinese medicinal plant, it has been proved to produces a variety of unique metabolites, such as glycosides, quinones, lignans, terpenes and flavonoids, with different bioactivities including antioxidant, anti-tumor, anti-diarrheal, anti-inflammatory, analgesic and antibacterial activities. Studies showed that endophytic fungi may secrete compounds that are similar to those of the host. Thus, the endophytic fungi of medicinal plants are important medicinal resources and are beneficial to the research and development of natural medicines. Therefore, studying the diversity of endophytic fungi in the medicinal plant of Berchemia polyphylla var. leioclada is of great significance to discovering new drugs. However, the endophytic fungi in Berchemia polyphylla var. leioclada have been poorly studied. This study investigates the endophytic fungi in Berchemia polyphylla var. leioclada from Guizhou Province, China. Two new species Diaporthe berchemiae and Colletotrichum berchemiae are introduced based on morphological characters and multi-locus phylogenetic analysis. This is the first report of endophytic fungi in the medicinal plant Berchemia polyphylla var. leioclada, which enhances our understanding of the endophytic fungi in the medicinal plant Berchemia polyphylla var. leioclada.